AB0728 Employment status and work disability in an asian cohort of systemic lupus erythematosus patients: Preliminary results. (23rd January 2014) - Lian, T.Y.; Kong, K.O.; Leong, K.P.; Tan, J.C.; Thong, B.Y.H.; Chng, H.H.; Chan, G.Y.L.; Koh, E.T.; Law, W.G.; Chia, F.L.A.; Tan, J.W.L.; Howe, H.S.
Abstract : Background: There is little data on work disability in Asian patients with SLE. Loss of work ability contributes to loss in productivity, increase in health care cost and also loss of self esteem which in turn can lead to anxiety and depression. Objectives: To determine the employment status, prevalence of work disability in a cohort of Asian SLE patients and to identify its predictors. Methods: We established our SLE registry in 2001. This follows about 1000 patients who are followed up according to a standard protocol by trained staff rheumatologists or trainees at regular 4-12 months. A cross-sectional questionnaire study was performed to evaluate the employment status of consecutive patients with SLE. The following parameters were collected: demographic, socioeconomic data, employment status including their history of having modified their job or having changed their job(s) and disease characteristics. Work disability was defined as failure to work due to SLE activity and its related complications. Results: 323 patients were surveyed (mean age 45.5±12.1years, 92.4% women, 90% of Chinese descent, mean SLE duration 15.8±11.1years). Majority were married (65.8%) and 82.8% earned below the median Singapore income of $5000 per month (2010 census) More than half the patients (55.3%) did not have health insurance. There were 62 patients who were not in the workforce at time of questionnaire (30 housewives, 31 student, 1 retiree) and hence were excluded. Of the 261 who were in the workforce, 78((29.9%) lost their working ability. 52 of these patients (67.1%) reported they stopped work earlier than they had wanted to. The self reported causes of inability to work were fatigue (43.9%) and joint pains or aches (36.8%). A significant number of patients who were work disabled also modified their work or had to change jobs. Of the 78 patients who were unable to work, 47/78 (60%) modified their jobs by doing lighter duties (36.4%), or doing fewer hours or going part time (41.9%). Thirty one patients (39.7%) also changed jobs prior to stopping work with 60.5% of patients having changed 2 jobs. Conclusions: Work disability is an important problem among SLE patients. The unemployment rate is high compared to the national unemployment rate of 2.2%. Majority of the the patients who were work disabled experienced a period of work instability before they stopped work. Disclosure of Interest: None Declared